Assessing Intergenerational Earnings Persistence Among German Workers - Friedhelm Pfeiffer; Philipp Eisenhauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In this study we assess the relationship between father and son earnings among (West) German Workers. To reduce the lifecycle and attenuation bias a novel sampling procedure is developed and applied to the German Socio-Economic Panel (SOEP) 1984-2006. Our preferred point estimate indicates that about 1/3 of the earnings differential in the labor market has been passed on from the generation of fathers to their sons.
Keywords: J62; J31; J21; 330; Intergenerational Mobility; Lifecycle; Permanent Earnings; Wages; Lohn; Lebenseinkommen; Generationenbeziehungen; Familiensoziologie; Deutschland